TEACHER'S EFFORT TO IMPLEMENT QUALITY CHARACTER IN EARLY CHILDHOOD - Konadi, Husrin; Ainy Rambe, Syarifah (Ta'dib: Jurnal Pemikiran Pendidikan, 2022)
A person's development is strongly influenced by the conditions of the local social and cultural environment, traditions, values, behavior of both parents, the way parents educate and treat them, various kinds of media, and various kinds of events experienced in their lives. This value places emphasis on forming an attitude of not being hasty or careless, but based on careful reflection and planning, this character is a very important indicator in assessing character and influencing the beliefs of others. This research is a type of qualitative descriptive research whose purpose is to find out how the teacher's efforts to instill quality character in early childhood in Simehate Kindergarten. The research location is in Simehate Kebayakan Kindergarten. The results showed that Simehate Kindergarten instills Quality Character begins. The conclusion of this study is the efforts made by teachers in instilling quality character in early childhood in Simehate Kindergarten, namely by providing guidance and direction in accordance with several aspects of education such as cognitive, psychomotor, socio-emotional, religious and moral. The supporting factor in the process of instilling quality character in early childhood at Simehate Kindergarten is the educational content that has been contained in the school curriculum on character, the supporting infrastructure for the implementation of character education is also adequate. In addition, the main factor that drives children to have quality character is their parents or guardians.